Desenvolvimento de biocompósitos de poli(ácido láctico) e óxido de zinco modificado por plasma para aplicação em engenharia de tecidos - Marega, Felippe Migliato (Universidade Federal de São Carlos, 2023)
The increase in the incidence of bone fractures and trauma with the aging of the population has been driving the development of materials for bone repair with better mechanical and biological properties. Therefore, the present study aimed to develop biocomposites of poly (lactic acid) (PLA) and zinc oxide (ZnO) for 3D printing of scaffolds to be used in bone tissue engineering. The ZnO sur-face treatment technique by plasma was applied as an alternative to control the catalytic effects of ZnO on the degradation of PLA matrix. The PLA/ZnOAM bio-composites functionalized with maleic anhydride (MA), with different treatment times, were processed using an internal mixer, and rheological analysis and 3D printing of scaffolds were carried out. The scaffolds were characterized for their microstructural, thermal, and biological properties. It was observed that the in-crease in ZnO promotes a decrease in viscosity and the ratio between elastic and viscous components of biocomposites. However, the presence of the surface functionalization of the ZnO made it possible for the viscosity to remain closer to pure PLA. Mechanical analysis showed that ZnOAM biocomposites presented the required elastic modulus for bone application, unlike the untreated samples. Additionally, PLA/ZnOAM scaffolds showed higher cell viability when compared with those obtained from composites without surface treatment of the filler (PLA/ZnO), but bioactivity was higher in the untreated samples. In summary, the particle functionalization with maleic anhydride presented itself as a possible technique for controlling degradation of PLA matrix by ZnO, enabling the devel-opment of scaffolds with mechanical and biological properties with high potential for application in bone tissue engineering.
Development of poly (lactic acid) and plasma-modified zinc oxide biocomposites for application in tissue engineering
Keywords: PLA; Óxido de zinco; Scaffold; Manufatura aditiva; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA